2018
DOI: 10.1002/aorn.12391
|View full text |Cite
|
Sign up to set email alerts
|

OR Air Quality: Is It Time to Consider Adjunctive Air Cleaning Technology?

Abstract: Patients undergoing surgery may be at risk for infection from airborne particles such as dust, skin scales, respiratory aerosols, and hair fibers emanating from multiple sources in the OR, including personnel, heater‐cooler devices, and surgical smoke. This risk is increased in surgical patients undergoing procedures involving implanted devices. Surgical personnel also are at risk from exposure to surgical smoke, which can contain viable viral particles including human papillomavirus infection. Air quality in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
0
4
0
1
Order By: Relevance
“…4 The Association of periOperative Registered Nurses recommends that the evacuation apparatus should be no more than 2 inches from the source of generated smoke during open surgical procedures. 28 In accordance with these data, our simple smoke evacuation system described in the present study is precisely designed so that the cautery tip is directly inserted into the suction tube, enabling very close contact with the operation area without leakage of surgical smoke.…”
Section: Discussionmentioning
confidence: 90%
“…4 The Association of periOperative Registered Nurses recommends that the evacuation apparatus should be no more than 2 inches from the source of generated smoke during open surgical procedures. 28 In accordance with these data, our simple smoke evacuation system described in the present study is precisely designed so that the cautery tip is directly inserted into the suction tube, enabling very close contact with the operation area without leakage of surgical smoke.…”
Section: Discussionmentioning
confidence: 90%
“…Walsh et al reported that air filtration and disinfection units that combine HEPA filtration and UV-C disinfection technologies significantly reduce total and viable particle counts in a highly controlled OR setting. 39 Hyeong et al reported that built-in filter ports have the potential to reduce emission of SS. 40…”
Section: Resultsmentioning
confidence: 99%
“…The Association of periOperative Regis tered Nurses (AORN) group are known to advocate for a safe and smoke-free OR environment. 9 They support the use of local exhaust ventilation, either by a central smoke evacuation system, portable smoke evacuation unit, wall suction with inline filter or laparoscopic evacuation/filtration system. For open surgery, the evacu ation apparatus should be no more than 2 inches from the source of generated smoke.…”
Section: Discussion In Surgery • Discussion En Chirurgie Discussionmentioning
confidence: 99%
“…It is also believed that without proper smoke evacuation measures, electrosurgical devices in procedures open to the OR can be more harmful than robotic or laparoscopic procedures with regard to exposure of uncontrolled surgical smoke emission. 9 Despite all the literature suggesting that surgical smoke can have potential harmful effects with prolonged exposure, compliance with best practice measures has been difficult. The recommendations from various organizations advocating for local exhaust ventilators and respiratory precautions have been poorly implemented for many reasons, such as cost, lack of equipment or repair parts, physician resistance, staff complacency and extra personal accommodation devices.…”
Section: Discussion In Surgery • Discussion En Chirurgie Discussionmentioning
confidence: 99%